Is home bias biased? New evidence from the investment fund sector - Claudia Lambert; Luis Molestina Vivar; Michael Wedow (European Central Bank (ECB), 2024)
Investment funds hold a disproportionately larger fraction of domestic relative to foreign stocks. Stock market development and familiarity (language and distance) are considered key determinants for home bias. The literature neglects however that investors often invest in foreign funds domiciled in financial centers. We use a "look-through approach" to account for this misclassification. First, we find substantially smaller home bias estimates compared to those in the literature. Second, the explanatory power of plausible home bias determinants is lower than previously documented. Third, familiarity only plays a meaningful role when investors are households, highlighting the role of investor sophistication.
Keywords: G11; G15; G23; 330; investment funds; cross-border portfolio; home bias; financial centers